Service-learning essentials : questions, answers, and lessons learned - Jacoby, Barbara, (The Jossey-Bass higher and adult education series., 2015)
Service-Learning Essentials is the resource you need to help you develop high-quality service-learning experiences for college students. Written by one of the field's leading experts and sponsored by Campus Compact, the book is the definitive work on this high-impact educational practice. Service-learning has been identified by the Association of American Colleges and Universities as having been widely tested and shown to be beneficial to college students from a wide variety of backgrounds.